Landscape presentation formats influence consumer’s preferences for origin and botanical variety of Spanish honey - Pilar Uldemolins; M. Teresa Maza; Tiziana de-Magistris (Agricultural and Food Economics)
Abstract Context and presentation format influence behaviour and information processing. This study investigates how presenting the honey production landscape through different formats (i.e. pictures, 2D video, and immersive 3D video) affects consumer preferences and willingness to pay (WTP) for honey. A hypothetical choice experiment shows that presenting the landscape before the choice task considerably impacts WTP estimates for the geographical origin and botanical variety attributes of honey. Additionally, significant differences emerge across presentation formats, indicating that the immersive 3D video creates more pronounced variations in WTP based on the geographical origin of honey. Methodologically, our study contributes to the literature by utilising a 360°-virtual reality video, thus enhancing the realism of the experiment. Empirically, we explore how landscape visuals influence the consumer choices of honey, potentially increasing WTP for geographically sourced honey.